Simulasi Hujan-Debit di DAS Kedung Larangan Menggunakan Software HEC-HMS - Masrurin, Fina Nuril; Maulidiyah, Afrikhatul (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Flooding is a problem that often occurs in Indonesia, especially in Bangil-Pasuruan area, where every year always inundates several sub-districts there, 3 sub-districts are often submerged with a depth around 30-50 cm. The Bangil sub-district area is downstream in Kedunglarangan Watershed, where upstream in the Prigen sub-district. With these problems, appropriate mitigation is needed, an approach study in form of flow analysis is needed to provide appropriate handling. The rainfall discharge simulation method is an important tool in hydrology, one of the models used is using HEC-HMS software. Rainfall - discharge simulation in Kedunglarangan Watershed using HEC-HMS software using SCS Curve-Number method on runoff volume, SCS unit hydrograph on direct runoff. In analysis using modeling parameters such as initial abrasion, curve number, and time lag. This study aims to analyze the maximum discharge with a certain return period that can be used a reference in flood mitigation planning. In this study, the peak discharge was found at a 2-year return period of 75.9m3/s, a 5-year return period of 120.5m3/s, a 10-year return period of 154.7m3/s, a 20-year return period of 202.7m3/s, a 50-year return period of 241.6m3/s, and a 100-year return period of 282.7m3/s.